2014
DOI: 10.1159/000369201
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Burn Treated with 2% Rebamipide Ophthalmic Suspension: A Case Report

Abstract: A 47-year-old man presented at the Ophthalmology Department of Saku City Asama General Hospital complaining of hyperemia and pain after industrial sodium hydroxide (approx. 40% concentration) had entered his left eye. With an epithelial defect of the bulbar and palpebral conjunctiva, ischemia of the inferior third of the limbal conjunctiva, a total corneal epithelial defect and mild corneal stromal opacity, the damage was determined as Roper-Hall grade III. 2% rebamipide ophthalmic suspension, which is used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“… 8 11 Rebamipide ophthalmic suspension has been reported to exhibit multiple pharmacological effects, such as promoting the secretion of both mucin in tear fluid and membrane-associated mucin, increasing the number of goblet cells, 8 , 9 restoring the barrier function of the corneal epithelium, 12 , 13 and anti-inflammatory activity. 14 It has been reported that rebamipide ophthalmic suspension is effective not only for dry eyes but also for other corneal diseases such as Sjögren’s syndrome, 15 persistent corneal erosion, 16 superficial limbic keratopathy, 17 alkaline corneal injury, 18 lid wiper epitheliopathy, 19 and lagophathalmos. 20 However, no reports have been published concerning the efficacy of rebamipide ophthalmic suspension for persistent corneal epithelial defects associated with diabetic keratopathy.…”
Section: Introductionmentioning
confidence: 99%
“… 8 11 Rebamipide ophthalmic suspension has been reported to exhibit multiple pharmacological effects, such as promoting the secretion of both mucin in tear fluid and membrane-associated mucin, increasing the number of goblet cells, 8 , 9 restoring the barrier function of the corneal epithelium, 12 , 13 and anti-inflammatory activity. 14 It has been reported that rebamipide ophthalmic suspension is effective not only for dry eyes but also for other corneal diseases such as Sjögren’s syndrome, 15 persistent corneal erosion, 16 superficial limbic keratopathy, 17 alkaline corneal injury, 18 lid wiper epitheliopathy, 19 and lagophathalmos. 20 However, no reports have been published concerning the efficacy of rebamipide ophthalmic suspension for persistent corneal epithelial defects associated with diabetic keratopathy.…”
Section: Introductionmentioning
confidence: 99%